Study Of Wire Arc Additive Manufacturing And Potential In Part Repair - Vasuthaven, Arvind Ganeesh (Universiti Sains Malaysia, 2021)
Additive manufacturing has commonly been used in many fields such as automotive, marine, construction and more. In this research, the type of additive manufacturing been used is by one of the wire arc additive manufacturing, which is MIG welding. During the deposition process, many parameters will influence the quality of the deposited material. Hence to identify the optimal parameters, this research has been conducted and three parameters that have been manipulated are the voltage, filler speed and feed rate. For each parameter, there will be three levels. A total of 27 experimental combinations have been produced. Taguchi has been used to simplify the 27 combinations to 9 equivalent combinations to simplify the parameters combination. Based on this parameter, several tests have been conducted to assess the deposited material to the intended application i.e., product repair. The assessment is made based on toughness test, hardness test, and microstructure observation. The microstructure analysis was used to analyse the grain size and the internal cracks or gap between the grain structures. Based on Taguchi method, the optimal parameters are at combination of 2 voltage, 1 mm/sec filler speed and 100 mm/sec feed rate and 6 voltage, 7mm/sec filler speed and 100 mm/min feed rate for weld-forged and weldmachined respectively.